Desain Pengiriman Data Gambar Menggunakan Gelombang Cahaya Tampak dengan Sel Surya Sebagai Detektor Cahaya - Wahid, Rendy M.; Ariani, Menik; Adnan, Assaidah (Universitas Andalas, 2025)
Visible Light Communication research that sends image data has not been widely published. Therefore, it is necessary to conduct an experiment on sending image data from a camera connected to an Arduino where the module process is run. In this study, image transmission uses pulse-width-modulation (PWM), namely 2-PWM and 4-PWM. On the transmitter side, it consists of an OV2640 camera sensor, laser and Arduino Uno R3 while on the receiver side it consists of a solar panel and Arduino Uno R3. A push button is used as a trigger to take a picture by the camera; the image file will be converted by Arduino into binary; the binary will be modulated by the frequency of the red laser that emits pulses to the solar panel. The solar panel will forward the signal to Arduino to be modulated back into the original binary. Binary data will be processed into image data back offline using a computer. The system can work at a maximum distance of 8 m when using the 2-PWM module technique and a maximum of 6 m when using 4-PWM. The size of the system performance is calculated from the bit-error-ratio (BER) value based on the binary data received at the receiver.